The battle of hackham heath ebook - Flanagan, John (Ranger's Apprentice: The Early Years, 2016)
John Flanagan, author of the bestselling Ranger's Apprentice fantasy adventure epic , delivers a second prequel to Ruins of Gorlan, the novel that started it all, with Halt and Crowley preparing for war against a near-unstoppable enemy   When the former Baron Morgarath escaped to avoid punishment for treason, an uneasy peace fell on Araluen. But Morgarath, now in hiding, is already planning his next move, recruiting an army of savage, overpowering beasts known as Wargals. Newly crowned King Duncan knows he must assemble his troops for battle.   To find out the full extent of Morgarath’s plan of attack, Halt prepares for a seemingly impossible task—climbing the deadly cliffs of the Mountains of Rain and Night and venturing deep into enemy territory to spy. After all, the winner of this war could be determined by one wrong move.   At the Battle of Hackham Heath, the fate of a Kingdom will be decided. This origin story of how Halt came to be Araluen’s most famous Ranger – and how war will decide the future of the next generation – will thrill Ranger’s Apprentice fans and new readers alike.